MICaps: Multi-instance capsule network for machine inspection of Munro's microabscess. (January 2022) - Pal, Anabik; Chaturvedi, Akshay; Chandra, Aditi; Chatterjee, Raghunath; Senapati, Swapan; Frangi, Alejandro F.; Garain, Utpal
Abstract: Munro's Microabscess (MM) is the diagnostic hallmark of psoriasis. Neutrophil detection in the Stratum Corneum (SC) of the skin epidermis is an integral part of MM detection in skin biopsy. The microscopic inspection of skin biopsy is a tedious task and staining variations in skin histopathology often hinder human performance to differentiate neutrophils from skin keratinocytes. Motivated from this, we propose a computational framework that can assist human experts and reduce potential errors in diagnosis. The framework first segments the SC layer, and multiple patches are sampled from the segmented regions which are classified to detect neutrophils. Both UNet and CapsNet are used for segmentation and classification. Experiments show that of the two choices, CapsNet, owing to its robustness towards better hierarchical object representation and localisation ability, appears as a better candidate for both segmentation and classification tasks and hence, we termed our framework as MICaps. The training algorithm explores both minimisation of Dice Loss and Focal Loss and makes a comparative study between the two. The proposed framework is validated with our in-house dataset consisting of 290 skin biopsy images. Two different experiments are considered. Under the first protocol, only 3-fold cross-validation is done to directly compare the current results with the state-of-the-art ones. Next, the performance of the system on a held-out data set is reported. The experimental results show that MICaps improves the state-of-the-art diagnosis performance by 3.27% (maximum) and reduces the number of model parameters by 50%. Highlights: Attempts to solve the clinical challenge of automatic inspection of Munro's Microabscess (MM). Presents a fully automated capsule network for SC layer segmentation and MM detection. Weakly supervised approach for localisation of SC layer's neutrophils. Reports several experiments and in-depth analysis of the proposed capsule network.